2019
DOI: 10.1002/mgg3.831
|View full text |Cite
|
Sign up to set email alerts
|

SOD3 overexpression alleviates cerebral ischemia‐reperfusion injury in rats

Abstract: BackgroundIschemic stroke is a deadly disease that poses a serious threat to human life. Superoxide dismutase 3 (SOD3, ECSOD) is the main antioxidant enzyme that removes superoxide anions from cells. This study aimed to investigate the effect of SOD3 overexpression on cerebral ischemia‐reperfusion injury in rats.MethodsGV230‐EGFP‐ECSOD, the recombinant SOD3‐overexpressed vector, was constructed by genetic engineering technology, and mesenchymal stem cells (MSCs) were infected with lentiviral packaging. In anim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…In the diagnosis or treatment of diseases such as brain injury, reducing the level of SOD2 protein in mouse hippocampal neurons can reduce brain damage caused by hypoxia/reoxygenation. Similarly, SOD3 reduces obesity and inflammation caused by high fat, as well as brain damage due to cerebral ischemia [ 46 , 47 , 48 , 49 ]. These suggested that SOD2 or SOD3 could serve as important reference indicators for brain injury.…”
Section: The Application and Research Status Of Sods In Medicine Food...mentioning
confidence: 99%
“…In the diagnosis or treatment of diseases such as brain injury, reducing the level of SOD2 protein in mouse hippocampal neurons can reduce brain damage caused by hypoxia/reoxygenation. Similarly, SOD3 reduces obesity and inflammation caused by high fat, as well as brain damage due to cerebral ischemia [ 46 , 47 , 48 , 49 ]. These suggested that SOD2 or SOD3 could serve as important reference indicators for brain injury.…”
Section: The Application and Research Status Of Sods In Medicine Food...mentioning
confidence: 99%
“…With an additional scaffold of human BDNF (brain-derived neurotrophic factor) linked to chitosan scaffolds, the modified MSCs adequately migrate to the target site, and induce tissue regeneration within the traumatic brain injury environment [113]. Again, SOD3-MSCs administration do not only reduce the infarct volume of ischemic stroke rats, but also significantly improve the neurological function [114]. The effects of exosomes extracted from hypoxic preconditioned MSCs on memory deficits in Alzheimer disease mice model have also been documented.…”
Section: Neurological Conditionsmentioning
confidence: 99%
“…Additionally, the overexpression of chemokine (C-X-C motif) receptor 4 (CXCR4) by transient transfection [ 266 ] or stable transfection [ 267 ] in MSCs promoted MSC mobilization and enhanced neuroprotection in a rat cerebral ischemia model [ 266 , 267 ]. Other studies have shown that the overexpression of SOD3 [ 268 ], HGF [ 269 ], IL-10 [ 270 ], CCL2 [ 223 ], NGN1 [ 271 ], NGR1 [ 272 ], TSP4 [ 273 ], ITGA4 [ 274 ], BDNF [ 275 ] and EGFL7 [ 276 ] as well as miR-138-5p [ 277 ] can enhance the immunomodulatory and neuroprotective effects of MSCs and significantly improve the recovery of motor functions when transplanted into a rat stroke model.…”
Section: Gene Transfer Into Mscs For Neurological Disease Treatmentmentioning
confidence: 99%